Efficacy of Cloth Face Mask in Reducing COVID-19 Transmission: A Literature Review - Rizki, Saraswati Anindita; Kurniawan, Andree (UI Scholars Hub, 2020)
Coronavirus disease 2019 (COVID-19) has become a public health concern. Preventive measures, such as wearing personal protective equipment, must be done. On April 2020, the Center for Disease Control stated cloth face mask was recommended to be used by the public. This systematic review aimed to eva - luate the efficacy of cloth face masks in reducing COVID-19 transmission and to compare the fabric material that suits best for a cloth face mask. Journals included were from databases such as Google Scholar, PubMed, search engines, and references from other studies. The MeSH keywords, such as